Sex differences in ventricular-vascular interactions associated with aerobic capacity - Barbara N. Morrison; Peter M. Mittermaier; Garth R. Lester; Michael E. Bodner; Anita T. Cote (Echo Research and Practice)
Abstract Background Aerobic capacity measured by maximal oxygen uptake (VO2max) is related to functional capacity and is a strong independent predictor of all-cause and disease-specific mortality. Sex-specific cardiac and vascular responses to endurance training have been observed, however, their relative contributions to VO2max are less understood. The purpose of this study was to evaluate sex-specific ventricular-vascular interactions associated with VO2max in healthy males and females. Methods Sixty-eight males and females (38% females, 35 ± 10y) characterised as recreational exercisers to highly trained endurance athletes, and free of chronic disease underwent a cycle ergometer to assess VO2max. Resting arterial compliance and echocardiographic evaluation of left ventricular (LV) structure and function were measured and indexed to body surface area. Results VO2max was similar between groups (54 ± 6 vs. 50 ± 7 ml/kg/min, p = 0.049). Indexed LV mass (LVMi) was higher (96 ± 15 vs. 81 ± 11, p = 0.001) in males versus females, respectively. Linear regression analysis revealed two models that were significantly associated with VO2max in males and females. In males, the two models included (1) longitudinal diastolic strain rate and LVMi (r2 = 0.31, p = 0.003) and (2) indexed end-diastolic volume (EDVi) and longitudinal diastolic strain rate (r2 = 0.34, p < 0.001). In females, the linear regression models included (1) LVMi, large arterial compliance, longitudinal systolic strain rate, and age (r2 = 0.69, p < 0.001) and (2) EDVi, large arterial compliance, longitudinal systolic strain rate, and age (r2 = 0.52, p = 0.003). Conclusion These findings reveal that while in both sexes, LVMi and LVEDVi are associated with VO2max, arterial compliance was also found to contribute to the variance in VO2 max in females, but not in males. Further, ventricular relaxation was a significant factor in aerobic capacity in males, while in females ventricular contraction was a significant factor.